Challenges in the Diagnosis of Multiple Sclerosis: A Case Report - Galinytė, Kristina; Butenytė, Gintarė; Žemgulytė, Gintarė; Makštienė, Jurgita; Balnytė, Renata (Acta medica Lituanica, 2026)
Introduction: Multiple sclerosis (MS) may present as a tumor-like, or tumefactive demyelinating lesion, that is indistinguishable clinically and radiologically from a brain tumor. This poses a diagnostic challenge.Case presentation: We present a case report of a 23-year-old woman who was hospitalized in the Neurosurgery Department for biopsy of a brain mass. She had been diagnosed with Hodgkin’s lymphoma at the age of 12, underwent surgery and chemotherapy, and had been in remission ever since. During her annual follow-up a magnetic resonance imaging (MRI) of the brain was performed that revealed a lesion in the right temporal lobe. It was interpreted as central nervous system (CNS) lymphoma. Before arranged neurosurgical intervention, a follow-up MRI scan revealed multiple new small lesions in both hemispheres. Biopsy was not performed, and the patient was referred to the Neurology Department for clarification of the diagnosis. No abnormalities were detected in the tests performed. Cerebrospinal fluid (CSF) was not tested due to the patient’s refusal to repeat the unsuccessful procedure. The patient was discharged from the hospital. Three months later she arrived at the Emergency Department abroad with impaired coordination and hypoesthesia on the right side of the body. Two MRI scans revealed a new lesion in the left posterior periventricular area. CNS lymphoma was suspected again. The patient received treatment with levetiracetam and dexamethasone. Upon her return, an MRI scan was repeated, which revealed an enlargement of the lesion. CSF testing showed indistinct oligoclonal bands. As CNS lymphoma could not be excluded, a lesion biopsy was performed after discontinuation of the steroids therapy. Histological examination excluded malignancy. Later an MRI scan was repeated that showed two new contrast-enhancing lesions. Relapsing-remitting multiple sclerosis (RRMS) diagnosis was confirmed and treatment with disease-modifying therapies (DMTs) was planned.Conclusions: Open-ring enhancement with little or no mass effect on MRI suggests a tumefactive demyelinating lesion (TDL). Moreover, TDLs tend to have a lower relative cerebral blood volume, and higher minimum and average apparent diffusion coefficient values compared to CNS lymphomas. Flow cytometry shows a monotypic B lymphoid population in cases of CNS lymphoma, not in MS.
Keywords: tumor-like multiple sclerosis; differential diagnosis; CNS lymphoma